EFFECT OF PSAK 72 IMPLEMENTATION IN PROPERTY AND REAL ESTATE’S FINANCIAL HEALTH - Fransisca, Juni; Ahalik, Ahalik (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2021)
PSAK 72 is set to become a single standard regulating revenue recognition and is effective starting January 1st, 2020. This standard has a significant impact on the property and real estate sectors. This study aims to compare the company's financial health before and after the application of PSAK 72 using the Springate and Taffler models. The ratios used to measure the comparison of income in this study are net profit margin and total asset turnover. The population used in the companiy's property and real estate listed on the Indonesia Stock Exchange in 2019-2020. By using a purposive sampling method, the research sample obtained 31 companies. The analytical tool used in this test is the Wilcoxon signed-rank test. The results showed a significant decrease in net profit margin and total asset turnover between before and after the implementation of PSAK 72 and the effect on financial health as measured by the Springate and Taffler models.